A Study of Sports Talent (Characteristics of Elite and Non-Elite Junior Tennis Athletes in Jambi City Based on Gender) - Nadia Nadia; Syahrial Bakhtiar; Oktarifaldi Oktarifaldi; Risky Syahputra; Lucy Pratama Putri (Universitas PGRI Palembang, 2023)
The biomotor skills held by junior tennis players in Jambi City were unknown at the time this research was done. Based on specific factors, this sort of research compares (compares) the results of 48 participants in a total sample. The anthropometry (height and weight), motion coordination (balance beam, jumping sideways, moving sideways, endurance shuttle run, and eye-hand coordination) and physical talents of junior tennis players were measured in order to determine their biomotor skills (shoulder rotation, sit and reach, standing broad jump, curl-ups, knee push-ups, 10x5m shuttle run and endurance shuttle run). Two-way analysis of variance (ANOVA) was used to assess the data with a 2x2 factorial design. The study that was carried out by the researchers produced the following findings: (1) In Jambi City, there were variations in the biomotor skills of elite and non-elite junior tennis players with a Sig value of 0.044 0.05. (2) There were biomotor differences between junior tennis players that were male and female with values Sig 0.000 0.05. (3) The athlete group and gender have an interaction on biomotor skills with a Sig value of 0.020 0.05.